To rewrite the equation \( \frac{4x}{3x - 12} + 3 = 10 \) in a more concise form, we can follow these steps:
-
Start with the original equation: \[ \frac{4x}{3x - 12} + 3 = 10 \]
-
Subtract 3 from both sides: \[ \frac{4x}{3x - 12} = 7 \]
Now, we can express this as two separate equations:
-
The first equation is: \[ \frac{4x}{3x - 12} = 7 \]
-
The second equation can be simplified to: \[ 3 = 3 \]
Therefore, the final concise version, focusing on the meaningful part, is: \[ \frac{4x}{3x - 12} = 7 \quad \text{and} \quad 10 - 3 = 7 \]
Alternatively, if you want to keep it simpler: \[ \frac{4x}{3x - 12} = 7 \quad \text{and} \quad 3 = 3 \]
However, since \(3 = 3\) is always true, you can just focus on the significant equation.